World Bank's Experience with Structural Reforms for Growth and Development - Swaroop, Vinaya (World Bank, Washington, DC, 2016)
The World Bank Group has come a long way in supporting structural reforms in its member countries. The most remarkable feature of its long 35 years and continuing journey has been its ability to listen, learn and adjust over time. It learnt relatively quickly that reform ownership is a necessary requirement for countries to support and sustain reforms. At the same time, it realized that reform implementation critically depends on credible institutions and good governance, which are frequently missing in its member countries, particularly the low-income ones. It also noted that over time the structure of reforms for promoting growth and development evolves, reflecting both changes in internal country conditions and a changing global environment. These important realizations are reflected in the evolution of the World Bank Group’s policies and practice for supporting structural reforms, and help sustain a culture of learning from experience.